Building an effective environmental management science program : final assessment (National Academy Press, 1997)
Assesses the Department of Energy's Environmental Management Science Program - a program that funds basic research related to environmental cleanup of the department's weapons complex. This book also provides recommendations on long-term challenges and opportunities for the program.
"This work was sponsored by the U.S. Department of Energy, Contract No. DE-FC01-94EW54069/R."--Title page verso
Keywords: National Research Council (U.S.). -- Committee on Building an Environmental Management Science Program.; National Research Council (U.S.). -- Committee on Building an Environmental Management Science Program; Environmental management -- Research -- United States.; Environnement -- Gestion -- Recherche -- États-Unis.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy.; Environmental management -- Research; United States; Recursos naturais e o ambiente (controle)